Helminth parasites in the endangered Ethiopian wolf, Canis simensis. Issue 4 (July 2015) - van Kesteren, F.; Piggott, K.J.; Bengui, T.; Kubri, S.B.; Mastin, A.; Sillero-Zubiri, C.; Paris, M.; Millar, R.P.; Macdonald, D.W.; Shiferaw, F.; Craig, P.S.
Abstract Ethiopian wolves, Canis simensis, are an endangered carnivore endemic to the Ethiopian highlands. Although previous studies have focused on aspects of Ethiopian wolf biology, including diet, territoriality, reproduction and infectious diseases such as rabies, little is known of their helminth parasites. In the current study, faecal samples were collected from 94 wild Ethiopian wolves in the Bale Mountains of southern Ethiopia, between August 2008 and February 2010, and were screened for the presence of helminth eggs using a semi-quantitative volumetric dilution method with microscopy. We found that 66 of the 94 faecal samples (70.2%) contained eggs from at least one group of helminths, including Capillaria, Toxocara, Trichuris, ancylostomatids, Hymenolepis and taeniids. Eggs of Capillaria sp. were found most commonly, followed by Trichuris sp., ancylostomatid species and Toxocara species. Three samples contained Hymenolepis sp. eggs, which were likely artefacts from ingested prey species. Four samples contained taeniid eggs, one of which was copro-polymerase chain reaction (copro-PCR) and sequence positive for Echinococcus granulosus, suggesting a spillover from a domestic parasite cycle into this wildlife species. Associations between presence/absence of Capillaria, Toxocara and Trichuris eggs were found; and egg burdens of Toxocara and ancylostomatids were found to be associated with geographical location and sampling season.